Electroacupuncture Alleviates Pain Responses and Inflammation in a Rat Model of Acute Gout Arthritis. (19th March 2018) - Chai, Wenxin; Tai, Yan; Shao, Xiaomei; Liang, Yi; Zheng, Guo-qing; Wang, Ping; Fang, Jianqiao; Liu, Boyi
Abstract : Acute gout arthritis is one of the most painful inflammatory conditions. Treatments for gout pain are limited to colchicine, nonsteroidal anti-inflammatory drugs, and corticosteroids, which oftentimes result in severe adverse effects. Electroacupuncture (EA) has been proved to be effective in relieving many inflammatory pain conditions with few side effects. Here, we aim to investigate the therapeutic potentials of EA on pain and inflammation of a rat model of acute gout arthritis and underlying mechanisms. We found that 2/100 Hz EA produced the most robust analgesic effect on mechanical hyperalgesia of acute gout arthritis rat model compared with 2 and 100 Hz. EA produced similar analgesic effect compared with indomethacin. 2/100 Hz EA also significantly alleviates the ongoing pain behavior, thermal hyperalgesia, and ankle edema. Locally applied μ and κ -opioid receptor antagonists but not adenosine A1 receptor antagonist significantly abolished the analgesic effect of EA. Locally applied μ and κ -opioid receptor agonists produced significant antiallodynia on acute gout arthritis rats, mimicking EA. Furthermore, 2/100 Hz EA upregulated β -endorphin expression in inflamed ankle skin tissue. Our results demonstrated, for the first time, that EA can be used for relieving acute gout arthritis with effect dependent on peripheral opioid system and comparable with the one obtained with indomethacin.